The impacts of microporous layer degradation on liquid water distributions in polymer electrolyte membrane fuel cells using synchrotron imaging - Liu, H.; George, M. G.; Zeis, Roswitha; Messerschmidt, M.; Scholta, J.; Bazylak, A. (ECS Transactions, 2017)
In this work, commercial gas diffusion layers (GDLs) both with and without microporous layers (MPLs) were degraded through an accelerated degradation process. Pristine and degraded GDLs were each assembled in a customized fuel cell to investigate MPL degradation impacts on the distribution of liquid water via synchrotron X-ray radiography. The presence of an MPL reduced the liquid water accumulation within the GDL, which provided benefits for the performance of the fuel cell. However, the MPL was more strongly affected by the degradation process compared to the carbon fiber substrate, leading to an increased mass transport resistance and a notable performance degradation. In the degraded GDL with an MPL, higher quantities of liquid water accumulated within the GDL, as well as at the catalyst layer/MPL, MPL/carbon fiber substrate, and GDL/flow field interfaces.
CRIS-Team Scopus Importer:2023-08-01